A patient‐derived xenograft and a cell line derived from it form a useful preclinical model for small bowel adenocarcinoma. (13th March 2020) - Yamano, Tomoki; Kubo, Shuji; Tomita, Naohiro
Abstract: Basic and clinical studies on small bowel adenocarcinoma (SBA) are limited due to the rare nature of this cancer. We established a patient‐derived xenograft (PDX) model from the tumor tissue of an advanced SBA patient with liver and peritoneal metastasis, and a cell line from the PDX. In the PDX model, compared to the control group, 5‐fluorouracil (5‐FU) treatment resulted in statistically significant tumor growth inhibition (TGI), while oxaliplatin (OHP) and irinotecan had no significant inhibitory effects. In combination with 5‐FU, OHP showed the highest rate of TGI. The IC50 for OHP was significantly lower than those for paclitaxel, gemcitabine, and trifluorothymidine in the PDX‐derived cell line when compared to in HT29, a colon cancer cell line. Genetic analysis of the patient tumor, PDX tumor, and the cell line demonstrated consistency in the microsatellite status and mutations in TP53, APC, HRAS, CSF1R, FGFR3, FLT3, PDGFRA, and RET genes. However, the PDX tumor alone had additional mutations, indicating that the PDX‐derived cell line may support the unstable genetic status of the PDX. Our findings confirmed the effectiveness of the combination of OHP and 5‐FU, which is a common treatment for advanced SBA and advanced colorectal cancer, in a preclinical model. This preclinical model of SBA can help in further understanding the biology of SBA. Abstract : Our data indicated that 5‐FU was the key drug for treatment and OHP alone had the additional effect in combination with 5‐FU.